Laser-induced modification of structure and shape of cartilage in otolaryngology and orthopaedics*Presented at the Fundamentals of Laser Assisted Micro- and Nanotechnologies (FLAMN-2016) International Symposium (Pushkin, Leningrad oblast, 27 June to 1 July 2016). (November 2017) - Sobol', E.N.; Baum, O.I.; Omel'chenko, A.I.; Soshnikova, Yu.M.; Yuzhakov, A.V.; Kas'yanenko, E.M.; Tokareva, A.V.; Baskov, A.V.; Svistushkin, V.M.; Selezneva, L.V.; Shekhter, A.B.
Abstract: We present the results of basic research in laser modification of tissues in otolaryngology (correcting the shape of nasal septum and larynx cartilages), cosmetology (correcting ear and nose shape), orthopaedics and spinal surgery (treatment of diseases of spine disc and joints). The physical processes and mechanisms of laser-induced relaxation of stresses and regeneration of tissues are considered. New results of studies in this fast-developing field of laser surgery are presented, in particular, the results of laser correction of costal cartilage shape in the process of making implants for the treatment of larynx stenosis and controlled regeneration of the hyaline articular cartilage.